Structure of the Arabidopsis thaliana TOP2 oligopeptidase. Issue 5 (1st May 2014) - Wang, Ruiying; Rajagopalan, Krithika; Sadre‐Bazzaz, Kianoush; Moreau, Magali; Klessig, Daniel F.; Tong, Liang
<x xml:space="preserve">Abstract</x> Thimet oligopeptidase (TOP) is a zinc‐dependent metallopeptidase. Recent studies suggest that Arabidopsis thaliana TOP1 and TOP2 are targets for salicylic acid (SA) binding and participate in SA‐mediated plant innate immunity. The crystal structure of A. thaliana TOP2 has been determined at 3.0 Å resolution. Comparisons to the structure of human TOP revealed good overall structural conservation, especially in the active‐site region, despite their weak sequence conservation. The protein sample was incubated with the photo‐activated SA analog 4‐azido‐SA and exposed to UV irradiation before crystallization. However, there was no conclusive evidence for the binding of SA based on the X‐ray diffraction data. Further studies are needed to elucidate the molecular mechanism of how SA regulates the activity of A. thaliana TOP1 and TOP2.